Penerapan Strategi Double Loop Problem Solving (DLPS) dalam Meningkatkan Hasil Belajar Matematika pada Materi Bangun Ruang oleh Siswa Kelas II SDN 101927 Sekip Lubuk Pakam - Jelita, Indah; Ramadhani, Mastari; Hariati, Emy (Medan Resource Center, 2024)
This study investigates the impact of the Cooperative Integrated Reading and Composition (CIRC) learning model on Indonesian language learning outcomes among fourth-grade students. Specifically, it examines: 1) the learning outcomes of students taught using the conventional method, 2) the outcomes of students taught using the CIRC model, and 3) the influence of the CIRC model on Indonesian language learning outcomes. The research employed a quantitative experimental approach with a quasi-experimental design, using pretest and posttest activities. Two groups were studied: an experimental class (15 students) that used the CIRC model, and a control class (15 students) that followed the conventional approach. The findings reveal a significant effect of the CIRC model on student performance, with an average score of 83.33 in the experimental group compared to 76.33 in the control group. The t-test results showed a significant difference (Sig.(2-tailed) = 0.00 < 0.05), confirming that the CIRC model positively influences learning outcomes.